2022
DOI: 10.1177/01614681221111433
|View full text |Cite
|
Sign up to set email alerts
|

Counternarratives as DisCrit Praxis: Disrupting Classroom Master Narratives Through Imagined Composite Stories

Abstract: Background/Context: In disability critical race theory (DisCrit) Classroom Ecology, Annamma and Morrison (2018a) offered invaluable direction for teachers by proposing constructs that address racism and ableism within the foundational components of the classroom—curriculum, pedagogy, resistance, and solidarity. These liberatory lenses offered a critical framework to conceptualize and achieve DisCrit-aligned teaching and learning. However, as of yet, critically conscious classroom teachers who seek to make DisC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Engaging DisCrit as both a tool for analysis and a theoretical framework, contributors to TCR interrogated the deployment of racism and ableism: in norms and standards of early childhood education (Beneke & Love, 2022); in racialized perceptions of ability in higher education (Mireles, 2022); in barriers to the profession associated with teacher certification and licensure exams (Schwitzman-Gerst, 2022); in race-evasive perspectives and ideologies perpetuating discipline disparities in schools (Tefera et al, 2022); and in state learning standards (Clark et al, 2022). Authors engaged with DisCrit Classroom Ecologies and DisCrit Solidarity 2 —applying the former to literacy contexts (Locke et al, 2022) and the latter to disabled girls of color in a youth prison (Cabral et al, 2022, 2023). Several articles examined DisCrit within teacher education, including Beneke et al (2022), who revealed ways that teacher candidates weaponized emotions to uphold hierarchies of race and ability, and Perouse-Harvey (2022), documented ways that DisCrit and critical theory can provide preservice teachers with language to discuss and confront racism and ableism in schools.…”
mentioning
confidence: 99%
“…Engaging DisCrit as both a tool for analysis and a theoretical framework, contributors to TCR interrogated the deployment of racism and ableism: in norms and standards of early childhood education (Beneke & Love, 2022); in racialized perceptions of ability in higher education (Mireles, 2022); in barriers to the profession associated with teacher certification and licensure exams (Schwitzman-Gerst, 2022); in race-evasive perspectives and ideologies perpetuating discipline disparities in schools (Tefera et al, 2022); and in state learning standards (Clark et al, 2022). Authors engaged with DisCrit Classroom Ecologies and DisCrit Solidarity 2 —applying the former to literacy contexts (Locke et al, 2022) and the latter to disabled girls of color in a youth prison (Cabral et al, 2022, 2023). Several articles examined DisCrit within teacher education, including Beneke et al (2022), who revealed ways that teacher candidates weaponized emotions to uphold hierarchies of race and ability, and Perouse-Harvey (2022), documented ways that DisCrit and critical theory can provide preservice teachers with language to discuss and confront racism and ableism in schools.…”
mentioning
confidence: 99%